Analysing growth and productivity in Syria by growth accounting - Hans Joachim Schalk (Westfälische Wilhelms-Universität Münster, Centrum für Angewandte Wirtschaftsforschung (CAWM), 2011)
This study investigates the performances of growth and productivity in Syria for the period 1985-2008 by means of growth accountings for the total economy and three major sectors, agriculture, industry, and services. Based on these analyses, guidelines for policies are suggested aiming at the targets for growth and employment as projected in the 11th Five-Year Plan of the economy for the period 2011-2015. The relative importance of the growth of physical capital and labour, of human capital and total factor productivity (TFP) is assessed. The study shows that much higher investments in physical and human capital per year are necessary than accomplished in the recent past in all sectors to achieve the projected growth targets of the Plan. Particularly in the industry sector negative TFP growth hampers growth of output and productivity in the global economy. Growth and reform policy should be focused in the planning period particularly on this sector in order to meet the requirements with respect to the growth and employment targets for the total economy in the Plan.
Keywords: 330; economic growth; productivity; growth accounting; investment; TFP